Preliminary study on drying of stingless bee pot pollen using novel fluidized bed dryer with swirling distributor - Luqman, Abdul Halim; Firdaus, Basrawi; Chong, Jia Zheng; Oumer, A. N.; Ahmmad Shukrie, Md Yudin; Mohd Hazwan, Yusof; Shaharin, A Sulaiman (EDP Sciences, 2018)
High moisture content in raw pot pollen increases the activity of microorganisms, thus promotes fermentation and causes rapid deterioration. Hence, the objective of this study is to dry stingless bees pot pollen by a novel fluidized bed dryer. The experimental analysis was conducted based on flowrate, airflow temperature, power consumption and sample mass. It was found that the mass of pot pollen can be reduced by 6.86 % in 30 minutes of drying operation. The temperature rise is also minimal up to average of 31.5 C. This significantly reduced the impact of drying not only to the nutrients, but also the flavour and aroma. Moreover, the total energy consumed is 212.57 Wh, which is considered low. Hence, this preliminary study showed the feasibility of drying pot pollen using a novel fluidized bed dryer.